Structural, analysis and optical studies of cadmium sulfide nanostructured - Abdulwahab, S. Z. Lahewil; Yarub, Al-Douri, Assoc. Prof. Dr.; Uda, Hashim, Prof. Dr.; Naser Mahmoud, Ahmed, Dr. (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/